3D QSAR Based Virtual Screening of Pyrido[1,2-a] Benzimidazoles as Potent Antimalarial Agents - Sharma, Kalicharan; Srivastava, Apeksha; Tiwari, Pooja; Sharma, Shweta; Shaquiquzzaman, Mohammad; Alam, M. M.; Akhter, Mymoona (Letters in Drug Design & Discovery, 2019)
Background: Development of novel antimalarial agents has been one of the sought areas in medicinal chemistry. In this study the same was done by virtual screening of in-house database on developed QSAR model. Methods: A six point pharmacophore model was generated (AADHRR.56) from 41 compounds using PHASE module of Schrodinger software and used for pharmacophore based search. Docking studies of the obtained hits were performed using GLIDE. Most promising hit was synthesized & biologically evaluated for antimalarial activity. Result: The best generated model was found to be statistically significant as it had a high correlation coefficient r2= 0.989 and q2 =0.76 at 3 component PLS factor. The significance of hypothesis was also confirmed by high Fisher ratio (F = 675.1) and RMSE of 0.2745. The model developed had good predicted coefficient (Pearson R = 0.8826). The virtual screening on this model resulted in six hits, which were docked against FP-2 enzyme. The synthesized compound displayed IC50 value of 0.27μg/ml against CQS (3D7) and 0.57μg/ml against CQR (RKL9). Conclusion: 3D QSAR studies reviled that hydrophobic groups are important for anti-malarial activity while H-donor is less desirable for the same. Electron withdrawing groups at R1 position favours the activity. The biological activity data of the synthesized hit proved that the pharmacophore hypothesis developed could be utilized for developing novel anti-malarial drugs.
Keywords: schrodinger software